“Albergo Diffuso” Model for the Analysis of Customer Satisfaction - Patrizia Gazzola; Daniele Grechi; Enrica Pavione; Paola Ossola (European Scientific Journal, ESJ, 2019)
This paper focuses on assessing the level of satisfaction of customers that had spent some part of their holidays in an eco-way style. This is an innovative form of hospitality that is represented by the “Albergo Diffuso”. The connection between this sustainable tourism model and the customers wellbeing is based on concepts which are directly connected with sustainability and environment in a rural destination. The data are related to 450 reviews which were selected randomly from two websites of reviews and are about 15 different Hotels (Albergo Diffuso model). The methodology of content analysis, with a successive application of regression model, has been used to understand the factors that influence the tourist’s opinion. It also identifies the role ofsustainability, innovation, and tradition for customers that spend their holiday in ADs. The hypotheses tested in the paper are associated with the features of the literature and the link with sustainability of this model. This study contributes to the literature by providing empirical evidence on the customers satisfaction factors of a new tourist model which is quite diffused in Italy and other parts of the world. This will help to understand if the elements highlighted in the literature are consistent with the reviews or if there are other factors. For example, the provision of physiological and safety needs are more important for tourists.